EXOTIC PLANTS OF HALIMUN SALAK CORRIDOR: MICRO-ENVIRONMENT, DETECTION AND RISK ANALYSIS OF INVASIVE PLANTS - Decky Indrawan Junaedi; Dodo - - (BIOTROPIA, 2014)
The research of exotic plant species detection and invasive plant risk analysis conducted in Halimun Salak corridor area. This study aims to do inventory of exotic plant species in this area and perform invasive plant risk analysis to the exotic plants found. The invasion risk assessment of detected exotic plants analyzed using Weed Risk Assessment (WRA) method. Moreover, analysis of multi-dimensional scaling (MDS) based on inequality performed on relative humidity, light intensity, and soil pH. There are eleven exotic plant species which consist of three tree species and eight species of herbs / shrubs. Lantana camara and Camellia sinensis are the exotic species with biggest and smallest WRA score respectively.Â  MDS analysis shows that exotic tree species have similar environmental variables. Moreover, environmental variables of Clidemia hirta are relatively different from other exotic species found in the Halimun Salak corridor.Recommendations for the management of invasive exotic plant species in the area are:Â  immediate management implementation, priority of eradication to exotics that have not been abundant but have a high risk score, two management options (gradual eradication or containment) should be considered for exotics with very high WRA score such as Ageratina riparina, Chromolaena odorata and Lantana camara.